INFLUENCE OF ACQUIRED L2 KNOWLEDGE AND EXPERIENCE ON L3 LEARNING IN LEXICAL-GRAMMATICAL EXCERCISES (Živi jezici: Journal for Foreign Languages and Literatures, 2018)
The paper examines the influence of previous knowledge and experiences of students from English as a first foreign language (L2) on learning German as a second foreign language (L3) in sixth grade primary school students whose mother tongue is Serbian (L1) in solving lexical and grammatical tasks, whereby the analysis of language structures in L2 and L3 is analyzed during the development of a specific task and indicates the importance of language awareness and language learning awareness. The basis of the paper is the didactics and methodology of tertiary languages, and the characteristics of teaching German as a second foreign language after English are considered (DaFnE concept). The results of the evaluation of the lexical task (which requires knowledge transfer) confirm the positive influence of L2 on L3 learning and the success of most L3 language students in solving the task, regardless of the level of reflection or language awareness. The results of the evaluation of the grammatical task (which requires the transfer of knowledge and strategies, ie inductive reasoning) confirm that the success in solving this task depends on the level of language awareness and awareness of language learning, ie reflection.
Keywords: English as L2; German as L3; transfer of knowledge and strategy; language awareness; language learning awareness